Relationship of Physical Activity and Vitamin D Levels in Elderly Women - Lorensia, Amelia; Jalmav, Marthy Meliana Ariyanti; Suryadinata, Rivan Virlando; Akbar, Muhammad Reza Aprililo (Global Medical & Health Communication (GMHC), 2024)
Older adults are at risk of vitamin D deficiency, especially in older women, due to a decrease in the hormone estrogen, which causes decreased bone density and increased risk of fractures. There is a relationship between vitamin D deficiency and lack of physical activity due to the storage of vitamin D in adipose tissue. Physical activity was measured using the International Physical Activity Questionnaire (IPAQ). The aim was to determine the relationship between physical activity and vitamin D in elderly women. This cross-sectional analytic observational study was conducted at Nursing Home X in Surabaya city from May to August 2023. The variables were physical activity (measured by IPAQ to estimate physical activity levels) and vitamin D level (measured by VIDAS® instrument to determine 25(OH) levels). The subjects were all women aged ≥60 years. The sampling technique uses the purposive sampling method. For an analysis of the relationship between physical activity levels and vitamin D levels, the Pearson correlation test was used with a ratio data scale. This research received 49 respondents. The average physical activity level was 1316.82±720.90, and most respondents had a moderate physical activity level of 44.90%. Vitamin D levels were ≤30 ng/ml for 46 respondents (93.87%). The results of the Pearson correlation test were obtained with a rvalue=0.089 and a significance value (Sig.) of 0.542. There was no significant correlation between physical activity and vitamin D levels. Other factors such as age, health conditions, and vitamin D intake can affect the results. Further research can be developed into measurements to examine physical activity in old age.